Analisis Pengaruh Pajak Hotel Pajak Restoran Dan Pajak Kendaraan Terhadap Pendapatan Asli Daerah Kabupaten Alor Tahun 2018-2022 - Gaimau, Mariam (Peneliti.net, 2023)
One-source revenue is revenue received by the local government of Alor Regency, which comes from sources within its own territory. This study aims to determine the effect of hotel taxes, restaurant taxes and vehicle taxes on Alor Regency regional original income for the period 2018-2022 researchers carry out research at the Revenue Agency District of Alor. This type of research is quantitative research with data collection techriques, namely observation, interviews, and documentation studies. This study is multiple linier regrestion while hypothesis testing is carried out, using the t test of 0,000 or 6%. Partially the restaurant tas has an effect on local revenue of Alor Regency for the 2018-2022 period as indicated by a significance value of the t test of 0,00 or 0% of 0,005. Simultaneously, hotel taxes, restaurant taxes, and vehicle taxes have an effect on local revenue in Alor Regency for the 2018-2022 period, which is indicated by a significance value of the F test of 0,000 or 0%.